Factores predictores de colecistectomía difícil en adultos. Hospital José María Velasco Ibarra. Tena, 2021 – 2022. - Rivera Córdova, Mayté Valentina (2022)
ABSTRACT Cholecystectomy consists of surgical intervention by which the gallbladder is removed as a standard treatment to treat multiple pathologies that affect this organ. Between 10 and 15% of cholecystectomies are difficult due to various complications, so it is essential to establish factors that can be predictors to prepare its execution, reducing the level of risk. Objective: To determine the most common predictive risk factors for difficult cholecystectomy in patients over 18 years of age at the José María Velasco Ibarra Hospital in the 2021-2022 period. Material and methods: A descriptive, non-experimental and cross-sectional investigation was carried out based on the analysis of 48 medical records of patients diagnosed with cholecystitis and cholelithiasis who underwent cholecystectomy and were considered problematic. The results were analyzed to establish direct linear regression between the factors considered predictors and difficult cholecystectomy. Results: Five statistically significant factors considered predictors of difficult cholecystectomy were found: age, gender, history of diabetes mellitus, obesity, and history of previous abdominal surgeries. Conclusions: Difficult cholecystectomy occurs in 15% of cases at the José María Velasco Ibarra Hospital in Tena, primarily moderate and severe according to Tokyo criteria, associated with common predictive factors previously considered to improve the level of preparation and avoid emergencies. Keywords: Difficult cholecystectomy, cholelithiasis, cholecystitis, predictive factors.